Formulation of phenol-formaldehyde wood adhesive using modified lignin from spent coffee grounds. - Naraga, Joe Marie B. (2024.)
The detrimental effects on humans and the environment caused by the utilization of phenol-formaldehyde wood adhesive have grown linearly with the increasing demand for engineered wood products. One possible solution to address that is the development of formaldehyde-free biobased adhesives. However, the majority of these studies are not economically viable and opted to at least, minimize the formaldehyde emission instead. One of these alternatives is through the incorporation of biobased materials such as lignin, which can be extracted from spent coffee grounds (SCG). In this study, the lignin from Spent Coffee Grounds was successfully extracted. The isolation of the SCG lignin was able to yield an average of 10.23% alkali lignin which was confirmed through solubility tests, UV-vis, and FTIR analyses. The isolated lignin was then modified for phenol-formaldehyde-based wood adhesive, and the modification process was proven to be successful using FTIR analysis and through the significant increase in phenolic-hydroxyl content from 2.56% to 5.02%. The parametric study using a two-level full factorial (2k full factorial) design revealed that low lignin loadings (5%), low mixing temperature (28 deg C), and low mixing time (0.5 hours) are the desired formulation parameters that yield the highest adhesive shear strength of 1.572 MPa. Moreover, increasing the lignin loadings had no significant difference in the adhesive shear strength. The shear strength of the formulated adhesive showed a decreasing trend when the mixing temperature was increased. Ultimately, the addition of modified SCG lignin enhanced the adhesive shear strength by up to 115% in comparison to 100% PF wood adhesive. These findings collectively suggest that modified SCG lignin can be incorporated into the formulation of PF wood adhesive.
Thesis (Undergraduate, Bachelor of Science in Chemical Engineering) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2024.
Keywords: Wood adhesive -- Coffee grounds